If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9-2x-6x=62
We move all terms to the left:
9-2x-6x-(62)=0
We add all the numbers together, and all the variables
-8x-53=0
We move all terms containing x to the left, all other terms to the right
-8x=53
x=53/-8
x=-6+5/8
| 11x-17=65=180 | | 32x+5=44x-9 | | 8w−8=80 | | f/4-5=-5 | | 3.2x+11=1.2x-1 | | -14=23r−14=23 | | 6÷y=2 | | 2(8-y)+3=17 | | (6x+4)+(3x+1)=5x | | r-14=23r−14=23 | | 6=7z−22 | | -2(z+5)=-14 | | -17+b=-21 | | -2x-6x=-63 | | 3=10x+20 | | 9v^2+29v=0 | | -28=n+(-11) | | 4j-71=79 | | -x=4x-50 | | 7(n+1)=21 | | 2c^2+2c-84=0 | | 180=-5+10x+9x+1 | | 2x=5-3x^2 | | x+(x*3/7)=180 | | 7n–5=10n+13 | | 4+6x+6x=-128 | | 7=b-(-15) | | 9x-2x+56=9x+34 | | -6(x+4)-5=5(x+4)-10 | | 2/x-8=-17 | | 15.67+0.13x=16.42+-0.08x | | –7b+7b=0 |